Preoperative Histopathological Grading and Clinical Staging Versus Surgico-Pathological Grading and Surgical Staging in Endometrial Carcinoma Patients: A Single Centre Retrospective Study (Global Journal of Medical Research, 2018)
Objectives: To compare the accuracy of tumor cell type, tumor grade, and staging pre - and postoperatively in patients with endometrial carcinoma. Materials and Methods: A retrospective analysis of 81 patients who were diagnosed with endometrial carcinoma and underwent hysterectomy at the 1st Affiliated Hospital of Chongqing Medical University from January 2015 to December 2016. Results: Endometrioid adenocarcinoma was the most common histological subtype with an agreement of 75.3% (61/81) on final pathology. The overall concordance rate between pre- and postoperative histological grade was 65.4% (53/81). 25.9% (21/81) patients had been upgraded while 8.6% (7/81) had been downgraded. The accuracy of clinical and surgical staging was 64.2% (52/81) with 22.2% (18/81) patients had been upstaged and 13.6% (11/81) down-staged. Conclusion: Tumor histology and grade, as well as the clinical staging, are only moderate predictors of the final surgical pathological outcome and surgical staging. The highly aggressive serous and clear cell carcinomas have been missed on endometrial samplings. Preoperative grade 1 and clinical stage II tumors had the lowest agreement when compared postoperatively. Cautious planning and patient counseling must be required regarding the surgical approach to endometrial cancer.
Keywords: endometrioid adenocarcinoma; serous carcinoma; clear cell carcinoma; histological grade and staging